Anthracycline Drugs on Modified Surface of Quercetin-Loaded Polymer Nanoparticles: A Dual Drug Delivery Model for Cancer Treatment. - Chabita Saha; Agrima Kaushik; Asmita Das; Sandip Pal; Debashis Majumder (PLoS ONE)
Polymer nanoparticles are vehicles used for delivery of hydrophobic anti-cancer drugs, like doxorubicin, paclitaxel or chemopreventors like quercetin (Q). The present study deals with the synthesis and characterisation of nano formulations (NFs) from Q loaded PLGA (poly lactic-co-glycolic acid) nano particles (NPs) by surface modification. The surface of Q-loaded (NPs) is modified by coating with biopolymers like bovine serum albumin (BSA) or histones (His). Conventional chemotherapeutic drugs adriamycin (ADR) and mitoxantrone (MTX) are bound to BSA and His respectively before being coated on Q-loaded NPs to nano formulate NF1 and NF2 respectively. The sizes of these NFs are in the range 400-500 nm as ascertained by SEM and DLS measurements. Encapsulation of Q in polymer NPs is confirmed from shifts in FT-IR, TGA and DSC traces of Q-loaded NPs compared to native PLGA and Q. Surface modification in NFs is evidenced by three distinct regions in their TEM images; the core, polymer capsule and the coated surface. Negative zeta potential of Q-loaded NPs shifted to positive potential on surface modification in NF1 and NF2. In vitro release of Q from the NFs lasted up to twenty days with an early burst release. NF2 is better formulation than NF1 as loading of MTX is 85% compared to 23% loading of ADR. Such NFs are expected to overcome multi-drug resistance (MDR) by reaching and treating the target cancerous cells by virtue of size, charge and retention.